Pemanfaatan Artificial Intelligence Dalam Implementasi Chatbot Helpdesk untuk Mendukung Layanan TIK Publik pada Instansi Pemerintahan - Kartini Kartini; Malabay Malabay; Riya Widayanti (Bulletin of Computer Science Research, 2025)
Public services in many government institutions are still traditional, characterized by slow processes, bureaucracy, and limited working hours. This condition makes it difficult for the public to obtain information quickly and accurately. This study aims to analyze the utilization of Artificial Intelligence (AI) in the form of chatbots as a digital innovation to improve the quality, efficiency, and accessibility of public services. The research method used is a qualitative approach through literature review, observation, and interviews with ICT Public Service staff or employees at government agency, as well as users from the community. The research findings, as presented in Table 1 in Discussion sub-chapter 3.4, show that chatbots are able to provide instant and consistent responses, operate more efficiently (saving human resources and time), respond within one minute (real-time, 24/7), support automation, and reduce the workload of government officials through interactive services available around the clock. However, key challenges remain, including limitations in natural language understanding, data security issues, and user resistance to new technologies. With appropriate development strategies and attention to digital literacy among citizens, AI-based chatbots have the potential to become an effective solution in supporting the transformation of public services toward smart, transparent, and citizen-oriented governance.